Transition Metal-Mediated Annulation Approaches for Synthesis of Arylnaphthalene Lignan Lactones - Park, Sooyoung; Kim, Jin-Hee; Kim, Seok-Ho; Shin, Dongyun (Frontiers in Chemistry, 2020)
Arylnaphthalene lignan lactones belong to a class of natural lignans and more than 60 analogs have been isolated. Their pharmacological activities as well as unique structural features have attracted considerable attention from medicinal and synthetic chemists. Since the first synthesis in 1895, many synthetic methodologies with ionic or pericyclic reaction mechanisms have been reported. Transition metal catalysts sometimes provide exceptional synthetic versatility for the syntheses of natural compounds. Recently, transition metal-mediated methodologies were investigated for the construction of basic scaffolds of arylnaphthalene lignan lactones. Five kinds of transition metal catalysts containing gold, manganese, nickel, palladium, and silver have been explored. Most of the metal catalysts successfully created arylnaphthalene lactones by intermolecular or intramolecular annulative cyclization. In this review, all reports of transition metal-mediated annulative construction of arylnaphthalene lignan lactones were compiled, and synthetic approaches, mechanistic aspects, and successful applications were discussed.